The effects of compiler optimizations in face recognition system - Shuhaizar, Daud; Khalib, Z.I.K; R. Badlishah, Ahmad; Mohamad Rizon, Mohamed Juhari (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org